Fragmentation of two soft cereal products during oral processing in the elderly: Impact of product properties and oral health status. (June 2019) - Assad-Bustillos, M.; Tournier, C.; Feron, G.; Guessasma, S.; Reguerre, A.L.; Della Valle, G.
Abstract: This study investigated the mechanisms of fragmentation leading to bolus formation during chewing in the elderly population for two cereal foods of different compositions and cellular structure: sponge-cake (SC) and brioche (B). For both products, mechanical properties were characterized by uniaxial compression and 3D cellular structure was determined using x-ray micro-tomography. Stress-strain curves showed two distinct ductile-like behaviors: product B underwent plastic deformation, whereas product SC displayed a hyper-elastic behavior. Twenty subjects aged 65 years and over with two different oral health conditions (poor vs satisfactory dental status, variable stimulated salivary flow rate) were asked to consume both products. Bolus particle size was determined at three different chewing stages through image analysis, and the resulting particle size distribution (PSD) curves were fitted by Gompertz model. The model parameters were related to bolus particle heterogeneity and fragmentation, thanks to their correlations with median particle size diameter D50 and interquartile ratio (D75 /D25 ), directly extracted from PSD curves. The use of model parameters allowed discriminating between chewing sequences for both products and revealed different fragmentation patterns: while SC boli exhibited a continuous particle size reduction during chewing, B displayed a combination of fragmentation and agglomeration. In addition, results showed that subjects with a satisfactory dental status produced significantly more degraded boli than those with a poor dental status. These results highlight distinct fragmentation mechanisms for these two soft products that were interpreted in relation to their differences in composition, structure and mechanical behavior. Graphical abstract: Graphical Abstract for "Cereal FOP fragmentation" by Assad-Bustillos et al.: The mechanisms of fragmentation of soft cereal foods during chewing are determined by image analysis and by fitting particle size distributions. This approach has allowed us to link food structure and mechanical behavior on one side, with the dental status of elderly on the other side.Image 1 Highlights: Particle size distributions of soft cereal food boli can be fitted by Gompertz model. Model parameters indicate bolus degradation and particles size heterogeneity. The mechanical properties of soft cereal foods explain boli fragmentation behavior. Dental status of the elderly impacts food fragmentation.